Molecular Methods for the Detection of Toxoplasma gondii Oocysts in Fresh Produce: An Extensive Review - Slana, Iva; Bier, Nadja; Bartosova, Barbora; Marucci, Gianluca; Possenti, Alessia; Mayer-Scholl, Anne; Jokelainen, Pikka; Lalle, Marco (Microorganisms, 2021)
Human infection with the important zoonotic foodborne pathogen Toxoplasma gondii has been associated with unwashed raw fresh produce consumption. The lack of a standardised detection method limits the estimation of fresh produce as an infection source. To support method development and standardisation, an extensive literature review and a multi-attribute assessment were performed to analyse the key aspects of published methods for the detection of T. gondii oocyst contamination in fresh produce. Seventy-seven published studies were included, with 14 focusing on fresh produce. Information gathered from expert laboratories via an online questionnaire were also included. Our findings show that procedures for oocyst recovery from fresh produce mostly involved sample washing and pelleting of the washing eluate by centrifugation, although washing procedures and buffers varied. DNA extraction procedures including mechanical or thermal shocks were identified as necessary steps to break the robust oocyst wall. The most suitable DNA detection protocols rely on qPCR, mostly targeting the B1 gene or the 529 bp repetitive element. When reported, validation data for the different detection methods were not comparable and none of the methods were supported by an interlaboratory comparative study. The results of this review will pave the way for an ongoing development of a widely applicable standard operating procedure.
Keywords: foodborne parasites; toxoplasmosis; zoonosis; Toxoplasma gondii; detection; ready-to-eat (RTE) salad; oocyst; fresh produce